PENGARUH PENGGUNAAN MINYAK IKAN LEMURU (Sardinella lemuru) DALAM PAKAN TERHADAP LEMAK ABDOMINAL AYAM JOPER - P. P. A. U. Dewi; I. M. Nuriyasa; M. Wirapartha (Jurnal Peternakan Tropika, 2025)
The purpose of this study was to determine whether the use of lemuru fish oil (Sardinella lemuru) in the ration mixture can affect abdominal fat in joper chickens. This study was conducted for 8 weeks at the Teaching Farm of the Faculty of Animal Husbandry, Udayana University, using 80 unsexed joper chickens of DOC age divided into 20 experimental cages. The study used a Completely Randomized Design (CRD) with 4 additional treatments of lemuru fish oil (0%, 2%, 4%, and 6%) in the ration, each repeated 5 times. The ration consisted of yellow corn, rice bran, fish meal, lemuru fish oil, bread waste, mineral mix, and table salt. The variables observed included slaughter weight, percentage of pad fat, percentage of mesenteric fat, percentage of ventricular fat and percentage of abdominal fat. The results of the study showed that the use of lemuru fish oil in joper chicken feed had a significant effect (P<0.05) on slaughter weight but had no significant effect (P>0.05) on the percentage of pad fat, mesenteric, ventricular and abdominal. Based on the research results, it can be concluded that the use of lemuru fish oil in feed has not been able to significantly reduce the percentage of pad, mesentery, ventricle and abdominal fat in joper chickens, but has a significant in increasing the slaughter weight of joper chickens at a level of 4% (P2). ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui apakah penggunaan minyak ikan lemuru (Sardinella lemuru) dalam campuran ransum dapat mempengaruhi lemak abdominal pada ayam joper. Penelitian ini dilaksanakan selama 8 minggu di Teaching Farm Fakultas Peternakan Universitas Udayana, menggunakan 80 ekor ayam joper unsexed umur DOC yang dibagi dalam 20 kandang percobaan. Penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan 4 perlakuan tambahan minyak ikan lemuru (0%, 2%, 4%, dan 6%) dalam ransum, masing-masing diulang 5 kali. Ransum terdiri dari jagung kuning, dedak padi, tepung ikan, minyak ikan lemuru, limbah roti, mineral mix, dan garam dapur. Variabel yang diamati meliputi bobot potong, persentase lemak bantalan, persentase lemak mesentrium, persentase lemak ventrikulus dan persentase lemak abdominal. Hasil penelitian penggunaan minyak ikan lemuru dalam pakan ayam joper berpengaruh nyata (P<0,05) terhadap bobot potong, tetapi tidak berpengaruh nyata (P>0,05) terhadap persentase lemak bantalan, mesentirum, ventrikulus dan abdominal. Berdasarkan hasil penelitian dapat disimpulkan bahwa penggunaan minyak ikan lemuru dalam pakan belum mampu menurunkan persentase lemak bantalan, lemak mesentrium, lemak ventrikulus dan lemak abdominal ayam joper, tetapi meningkatkan bobot potong ayam joper pada level pemberian 4% (P2).